Silica nanoparticles induce start inhibition of meiosis and cell cycle arrest via down-regulating meiotic relevant factors. Issue 5 (2nd August 2016) - Zhang, Jin; Ren, Lihua; Zou, Yang; Zhang, Lianshuang; Wei, Jialiu; Li, Yanbo; Wang, Ji; Sun, Zhiwei; Zhou, Xianqing
Graphical Abstract: Abstract: Silica nanoparticles have been shown to induce reproductive toxicity, but the mechanism is unknown. To investigate the toxic mechanism of SiNPs, 60 male mice were randomly divided into three groups: a control group, a saline group and a SiNPs group, with two evaluation time points (45 and 75 days after the first dose) per group. Mice in the SiNPs group were treated with SiNPs at a dose of 2.0 mg kg −1 every three days, a total of 15 times in 45 days, mice in the saline group were given the same volume of physiological saline, and the control group was treated with nothing. Then, half of the mice in each group were sacrificed for tissue samples on days 45 and 75. In vitro, GC-2spd cells were exposed to various concentrations of SiNPs for 24 h. The results showed that SiNPs damaged seminiferous epithelium, leading to a decrease in sperm quality and an increase in the sperm abnormality rate. Moreover, expressions of Sohlh1/cyclin A1/cyclin B1/CDK1/CDK2 were greatly down-regulated and the ROS level in the testicular tissue of the mice was significantly increased on day 45. However, these changes were reversed by day 75. In vitro, SiNPs induced G0/G1-phase cell cycle arrest and proliferation inhibition in GC-2spd cells. These results suggested that SiNPs might induce cell cycle arrest and inhibit cell proliferation by down-regulating expressions of meiotic regulators, whereas DNA damage caused by oxidative stress may be associated with meiosis and sperm production. In addition, damage to the male reproductive system caused by SiNPs may be reversible.